"The King Is Dead, Long Live The King!": Image of the United States as the Primary Enemy on the Pages of Krokodil from Stalin to Khrushchev. Issue 1 (2nd January 2016) - Mammadov, Rashad
Abstract : The relationship between the Soviet Union and United States during the early Cold War has been analyzed from many different angles, but the research's primary focus has been on the political events that occurred and the statements made by political figures. Many scholars have looked at the Khrushchev period of Soviet history; however, a lack of attention has been paid to the role of the media as a mirror of political processes. Even fewer studies compare media realities across the Stalin and Khrushchev periods. Although a strongly declared attempt to cooperate with the Western world was the key characteristic of Khrushchev's Thaw, this study assumes that the true approach of the Soviet political establishment toward the United States was even more radical than Stalin's approach. A semiotic textual analysis of the cartoons of the Krokodil illustrated satirical magazine has found a trend of negative visual portrayals of the United States as the primary enemy of the citizens of the Soviet Union . This article alludes to dozens of cartoon images. Figures labelled with an 'o' are available for reference onvcquarterly.org .